Academic and recreational reading attitudes among primary students in a rural Malaysian village - Astri Yulia; R. Malatesha Joshi; Nor Azilah Husin; Na Thinamalar Magiswary Nadarajan; Norhayati Mohd Zin; Cheli Nadarajan (Universitas Syiah Kuala, 2024)
Reading is crucial for development and educational outcomes, yet access to literacy resources and supportive environments is uneven, particularly in rural and low-income areas. Positive reading attitudes are linked to better reading achievement, but research on these attitudes among ESL speakers in non-Western, rural contexts remains limited. This study explores the attitudes of 4th and 5th graders towards recreational and academic reading in a rural Malaysian village, assessing students who participated in a reading program. Utilizing the Elementary Reading Attitude Survey, data were gathered from 74 of the 120 participants, achieving a 62% response rate. Analysis through Partial Least Squares Structural Equation Modeling (PLS-SEM) revealed a nuanced relationship between childrens reading attitudes and their engagement with various reading contexts and activities. Findings underscore a pronounced preference for recreational over academic reading, with both types of reading attitudes significantly interrelated. This suggests the programs environment and involvement of reading partners may significantly shape childrens reading perceptions. Moreover, the study highlights the pivotal role of the reading context, indicating a direct correlation between childrens positive perception of their reading environment and their engagement levels. While the study did not delve into the impact of socio-economic status on program effectiveness, it signals the need for further research across diverse cultural settings to fully understand the efficacy of reading programs. The research concludes that after-school reading initiatives are instrumental in enhancing childrens academic and recreational reading attitudes, providing valuable insights for educators, policymakers, and researchers focused on literacy development.